2017
DOI: 10.1186/s12906-017-1740-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 16-week Bikram yoga program on heart rate variability and associated cardiovascular disease risk factors in stressed and sedentary adults: A randomized controlled trial

Abstract: Background: Chronic activation of the stress-response can contribute to cardiovascular disease risk, particularly in sedentary individuals. This study investigated the effect of a Bikram yoga intervention on the high frequency power component of heart rate variability (HRV) and associated cardiovascular disease (CVD) risk factors (i.e. additional domains of HRV, hemodynamic, hematologic, anthropometric and body composition outcome measures) in stressed and sedentary adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…To further substantiate the potential beneficial effect of prolonged Tai Chi/Yoga training for autonomic nervous function, a growing number of experimental studies have recently been conducted [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. As the number of trials increases, two research groups attempted to systematically evaluate the existing literature regarding the effects of Tai Chi [ 34 ] or Yoga [ 35 ] on HRV. However, they either used qualitative synthesis [ 34 ] or meta-analyzed data about expiratory-to-inspiratory ratio, with inclusion of all age group and acute effects of yoga [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further substantiate the potential beneficial effect of prolonged Tai Chi/Yoga training for autonomic nervous function, a growing number of experimental studies have recently been conducted [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. As the number of trials increases, two research groups attempted to systematically evaluate the existing literature regarding the effects of Tai Chi [ 34 ] or Yoga [ 35 ] on HRV. However, they either used qualitative synthesis [ 34 ] or meta-analyzed data about expiratory-to-inspiratory ratio, with inclusion of all age group and acute effects of yoga [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the number of trials increases, two research groups attempted to systematically evaluate the existing literature regarding the effects of Tai Chi [ 34 ] or Yoga [ 35 ] on HRV. However, they either used qualitative synthesis [ 34 ] or meta-analyzed data about expiratory-to-inspiratory ratio, with inclusion of all age group and acute effects of yoga [ 35 ]. In particular, study findings of the meta-analysis [ 35 ] were not significantly supportive of the effects of Yoga on the selected HRV parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Christa E et al 4 observed in their study in frequency domain indices Our finding shows backward bending is superior to forward bending and should be included in lifestyle intervention to reduce stress and anxiety disorder; also reported by Chu I.H et al 5 in his study that a 12-week yoga program was effective in increasing parasympathetic tone and reducing depressive symptoms and perceived stress in women with elevated depressive symptom. Prevesioly Hewett ZL et al 6 found that a 16-week Bikram Yoga program did not increase the high-frequency power components of HRV.…”
Section: Discussionmentioning
confidence: 98%
“…Many of the previous trials were conducted in healthy or normotensive populations [5][6][7][8][9][10][11][12][13][14], recruited participants from the workplace [9,11,15] or academic settings [8,10], and used the respective centres [8][9][10][11]14,16] or separate yoga studios [17][18][19] for the intervention. However, little evidence is available to demonstrate the impact of health-worker-led yoga interventions on blood pressure reduction in low-resource, primary care settings.…”
Section: Introductionmentioning
confidence: 99%